Behaviour of a SPD switchable glazing in an outdoor test cell with heat removal under varying weather conditions. (15th October 2016) - Ghosh, Aritra; Norton, Brian; Duffy, Aidan
Highlights: Outdoor performance of SPD glazing was done using a test cell with heat removal. Dynamic behaviour of SHGC was calculated from the measured data. Cooling load reduction potential of SPD glazing was investigated. Abstract: Suspended particle device (SPD) switchable glazing has potential to control transmission of solar radiation in the visible range by changing its transparency from 55% to 5%. Outdoor test cell characterisation of a SPD switchable glazing offered the dynamic solar heat gain coefficient (SHGC) which varied between 0.05 (when opaque) and 0.38 (when transparent). Reduction of maximum temperature rise of 11% and 15% was possible using SPD "transparent" and "opaque" state compared to same area double-glazing. Insulated test cell with water flow heat exchanger was employed to measure the cooling load reduction potential of SPD glazing while its transmission changed from "transparent" to "opaque" state. A cooling load reduction up to 6 kW h for a 0.343 m 3 volume test cell was possible by changing a 0.21 m × 0.28 m SPD glazing transparency from "transparent" to "opaque". Average overall heat transfer coefficient of SPD glazing varied between 5.02 W/m 2 K and 5.2 W/m 2 K for two different states.